Space and time, matter and mind : - Schommers, W. (World Scientific, 1994)
In principle, the elements of space and time cannot be measured. Therefore, the following question arises: how are reality and space-time related to each other? In this book, it is argued, on the basis of many facts, that reality is not embedded but projected onto space and time. We can never make statements about the actual reality outside (basic reality), but we can "only" form pictures of it. These are pictures of the same reality on different levels. From this point of view, the "hard" objects (matter) and the products of the mind are similar in character.